A comprehensive transfer program from pediatrics to adult care for parents of adolescents with chronic illness (ParTNerSTEPs): study protocol for a randomized controlled trial - Ena Lindhart Thomsen; Kirsten Arntz Boisen; Signe Hanghøj; Helena Hansson; Heidi-Christina V. Grabow Scheelhardt; Susanne Thing Christensen; Bente Appel Esbensen (Trials, 2022)
Abstract Background Previous research shows that adolescents with a chronic illness have more successful transfers to adult care if their parents are involved during the transition. However, there is a lack of structured and evaluated transfer programs for parents. Our aim will be to test a comprehensive transfer program for parents of adolescents with chronic illness during the transfer from pediatric to adult care and to evaluate the program’s effectiveness, acceptability, and costs. Methods The overall design for this protocol will be a randomized controlled trial. A total of 62 dyads consisting of an adolescent (age 16.5–17.5) and at least one parent will be recruited from one of four pediatric outpatient clinics (nephrology, hepatology, neurology, or rheumatology) at Copenhagen University Hospital - Rigshospitalet, Denmark. The dyads will be randomized to receive the transfer program in addition to usual care or to receive usual care only. The program includes an informative website, bi-annual online educational events, and transfer consultations across pediatric and adult care. Outcome measures will include transition readiness, allocation of responsibility, parental uncertainty level, and transfer satisfaction. Data will be collected from participants at baseline, every 6 months until transfer, at transfer, and 3 months after transfer. The parents’ acceptance of and satisfaction with the program will be explored through semi-structured interviews. Cost, barriers, and facilitators affecting future implementation will be identified in interviews with health care professionals, using the Normalization Process Theory as a framework for the process analysis. Discussion To our knowledge, this transfer program is one of the first interventions for parents of adolescents with a chronic illness during their child’s transfer to adult care. Our trial will include parental and adolescent measures allowing us to examine whether a transfer program for parents will improve transfer to adult care for both parents and adolescents. We believe that results from our trial will be helpful in forming recommendations to ensure better involvement of parents in transitional care. Trial registration ClinicalTrials.gov NCT04969328 . Retrospectively registered on 20 July 2021.